Software design ARM "Medical and educational station" - Zhanys, Aray (Рroblems of engineering and professional education, 2023)
By analyzing the nature of information systems professional determine their often as professionally-oriented small computer system situated directly in the workplace specialists and designed for the automation of their work. For cach object management is necessary to provide workstations corresponding to their functional purpose. However, the principles of IP should be common: consistency, flexibility, stability, and efficiency.